Study on Effect of Process Variable on Fastening Quality Using Process Monitoring Data of Flow Drill Screwed 590DP Steel/AA5052 combination - Kang, Tae-Young; Lee, Han-ju; Abdul, Karim Md; Nam, Dae-Geun; Lee, Byeong-ryong; Choi, Jung-Muk; Park, Yeong-Do (Journal of Welding and Joining, 2022)
The reduction of the weight of a vehicle body to improve fuel efficiency has been garnering widespread interest in the automobile industry. As the use of lighter materials increases, the joint of the dissimilar materials becomes crucial to guarantee the rigidity of the vehicle body. Amongst the joining methods for various multi-materials, the flow drill screw (FDS) is a fastening method that can mechanically join two or more plates using fasteners at high speed with a one-sided approach. Several studies have been conducted on the FDS joint quality with process parameters. However, a majority of them are focused on similar aluminum combinations and joint quality with various rotation speeds and downforce. The monitoring data analysis for the FDS joint of 590DP Steel/AA5052 combination and its fastening quality with the various process variables has been investigated in this study. The downforce and feed rate affect the process time required for the penetration stage. The maximum temperature reached during the process decreases as the downforce and feed rate increase. In addition, the critical torque value must be satisfied to ensure a defect-free joint. The combination of the downforce, feed rate, and torque affect the size of the gap at the joint interface. A high torque value can reduce the gap in the final tightening step. However, the joint strength of the FDS did not show differences with the gap. All the joints failed the pull-out mode when the fastener was released from the lower aluminum sheet.